2022
DOI: 10.7124/bc.000a75
|View full text |Cite
|
Sign up to set email alerts
|

N-alkyl functionalized squaraine dyes as fluorescent probes for the detection of serum albumins

Abstract: Here we synthesize a series of benzoindolium squaraine dyes with N-substituents (SQ) and examine these dyes as fluorescent probes to detect serum albumins. Methods. Organic synthesis, fluorescent spectroscopy, absorption spectroscopy, fluorescent microscopy. Results. The spectralluminescent properties of SQ dyes in the aqueous solution were investigated in the presence of bovine serum albumin (BSA), human serum albumin (HSA), equine serum albumin (ESA), ovalbumin (OVA), beta-lactoglobulin (BLG) and lysozyme (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…At the same time, the shape of the dye 2412 absorption spectrum broadens (520-750 nm) with a new peak in the short wavelength regions and a low extinction coefficient value, which probably indicates the dye aggregation in water. In our previous work, we showed that no evidence of the aggregate destruction was observed after a change in concentration of dye 2412 [27]. However, the destruction of the aggregates was observed after the dissolving of dye 2412 in the BSA solution.…”
Section: Spectral-luminescent Properties Of Squaraine Dyesmentioning
confidence: 84%
See 1 more Smart Citation
“…At the same time, the shape of the dye 2412 absorption spectrum broadens (520-750 nm) with a new peak in the short wavelength regions and a low extinction coefficient value, which probably indicates the dye aggregation in water. In our previous work, we showed that no evidence of the aggregate destruction was observed after a change in concentration of dye 2412 [27]. However, the destruction of the aggregates was observed after the dissolving of dye 2412 in the BSA solution.…”
Section: Spectral-luminescent Properties Of Squaraine Dyesmentioning
confidence: 84%
“…In our previous work [27], we reported the spectral-luminescent properties of N-substituents benzoindoliumsquaraine dyes and their interaction with albumins of different structures. All studied dyes in complexes with serum albumins demonstrated an increase in fluorescence emission intensity compared to the free state in an aqueous solution.…”
Section: Molecular and Cell Biotechnologiesmentioning
confidence: 99%
“…At the same time, the shape of the dye 2412 absorption spectrum broadens (520-750 nm) with a new peak in the short wavelength regions and a low extinction coefficient value, which probably indicates the dye aggregation in water. In our previous work, we showed that no evidence of the aggregate destruction was observed after a change in concentration of dye 2412 [27]. However, the destruction of the aggregates was observed after the dissolving of dye 2412 in the BSA solution.…”
Section: Spectral-luminescent Properties Of Squaraine Dyesmentioning
confidence: 84%
“…In our previous work [27], we reported the spectral-luminescent properties of N-substituents benzoindoliumsquaraine dyes and their interaction with albumins of different structures. All studied dyes in complexes with serum albumins demonstrated an increase in fluorescence emission intensity compared to the free state in an aqueous solution.…”
Section: Molecular and Cell Biotechnologiesmentioning
confidence: 99%
“…і здатність проникати крізь клітинну мембрану розглянуто в роботі [10]. Вибір бензоіндоленінової кінцевої групи зумовлений тим, що барвники на її основі малотоксичні, зокрема широковживаний у медицині індоціанін зелений (indocyanine green (ICG)) [11], задовільно розчинні у фізіологічному розчині і мають високі квантові виходи флуоресценції.…”
unclassified